THE INTERNAL AND EXTERNAL FACTORS OF THE PROTAGONIST’S REPENTANCE IN THE MOVIE SCRIPT SECOND ACT BY JUSTIN ZACKHAM AND ELAINE GOLDSMITH-THOMAS - Susi Ekalestari; Alma Rizka Siregar (Universitas Islam Sumatera Utara, 2021)
This research is conducted to analyze the internal and external factors of the protagonist’s repentance from Second Act movie written by Justin Zackham And Elaine Goldsmith-Thomas. The internal factors of repentance are self evaluation, self-motivation, self-control, knowledge, regret, hatred towards the sin, and returns to god’s power and will. The external factors of repentance are peer support, social support, intense guidance, and stimulus. It is in accordance to the theory proposed by Fachitiandi. This study uses qualitative descriptive method because the process and the result are accomplished descriptively and the focus goes to the analysis of social phenomena conducted and experienced the main character. Repenteance is not only found in a literary text but also in social reality, therefore this research is important enough for the readers to maintain a good life by avoiding things contrary to social norms. After the analyzing, it is found that internal factors of the Protagonist’s repentance in the movie script are self-evaluation, self-motivation, and knowledge, while, the external factors of the protagonist’s repentance are peer of support and social of support.